Analysis of Translation Teaching Strategies by English Teacher in High School during Corona Period - Trenady Iswandana; Maria Novesia Situmeang; Veronika Anastasya br Purba (Jurnal Ilmiah Wahana Pendidikan, 2021)
Along with the development of teaching methods, it becomes an important reference in the concept of processing teaching techniques for students, especially for high school students. Translation is a reason to improve students' language skills. Translation is a delivery process whose purpose is to change the written text in the source language into the most acceptable target language text. Therefore, it is necessary to understand the syntax, semantics and pragmatics as well as the ability to analyze the source language.. The use of translation in the teaching process during the corona pandemic period became one of the real challenges for teachers as teaching staff in packaging learning methods so that students could understand and apply them in the real learning process. The research uses quantitative methods by using questionnaires in collecting data from several high school teachers. Teachers always evaluate students' translation skills by using suitable assignments or translation texts or stories. Overall, this research was quite challenging to do because it not only had to understand about translation teaching strategies but also because the epidemic situation made data collection difficult.